Artesania do tempo em Terra Sonâmbula de Mia Couto - Sarubbi, Gabriela Martins (2008)
The subject developed in this work concerns to the various forms that temporality can assume inside of a narrative fiction. The novel that serves of corpus for the study is Terra Sonâmbula, of the Mozambican author, Mia Couto. It was made an analysis of both narrative blocks of the novel Capítulos and Cadernos de Kindzu as well as of the characters and their performance, in each one of the blocks studied. The research aims to show the diference that temprality assumes in each one of the narrative blocks studied. We based ourselves on the work of some theoreticians who have been studying about time in the novel, in order that we could get a stronger relevance about the refered subject. Some of them threats the subject in a general way, while others look at it in a specific one, focusing African literatures written in Portuguese language